A influência da testosterona nas glândulas reprodutivas acessórias de Artibeus planirostris (Chiroptera: Phyllostomidae) - Puga, Cintia Cristina Isicawa [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
Chiroptera is the second largest order of mammals. This presents different reproductive strategies with some unique characteristics. However, there are very few reports related to the accessory reproductive glands (GRAs) of Brazilian bats. Artibeus planirostris (Phyllostomidae: Chiroptera) has a prostatic complex comprised of two regions (ventral and dorsal) and a pair of bulbourethral glands. The prostatic complex of this species shows variations during the year in: weight, epithelial height, percentage of components glands (lumen, epithelium and stroma), the amount of cells: positive androgen receptor and proliferation and death, as well as variations hormonal. Indicating that testosterone levels influence these variations. Castration (testosterone suppression) and subsequent supplementation of this hormone may elucidate the relationship of the GRAs with testosterone. Thus, the aim of this study was to evaluate the effect of castration and testosterone supplementation in GRA of A. planirostris. The animals were collected in the city of São José do Rio Preto, in the northwest of São Paulo State, Brazil. The captures were concentrated in the summer (21 st December to 21st March) in order to minimize variations arising from seasonality. The bats were aged as adults based on body weight, complete ossification of the metacarpalphalangeal epiphyses, wear of the teeth, positioning of the testes and the presence of sperm inside the testes, cauda epididymis and/or urethra. Thus, forty-six sexually male mature specimens were analyzed. Eight groups were formed: I) 3 days castrated (CA3d, n=7); II) 3 days control (CO3d, n=4); III) 15 days castrated (CA15d, n=7); IV) 15 days control (CO15d, n=5); V) 15 days castrated with testosterone cypionate (1µg/Kg/day) repositioned for 3 days (T3d, n=7); VI) 15 days castrated with testosterone cypionate (1µg/Kg/day) repositioned for 7 days (T7d, n=7); VII) Control of...

Chiroptera é a segunda maior ordem de mamíferos. Esta apresenta diferentes estratégias e características reprodutivas únicas. Entretanto, são raros os relatos relacionados com as glândulas reprodutivas acessórias (GRAs) masculinas de morcegos brasileiros. Artibeus planirostris (Phyllostomidae: Chiroptera) apresenta um complexo prostático compacto composto por duas regiões (ventral e dorsal) e um par de glândulas bulbouretrais. O complexo prostático desta espécie apresenta variações durante o ano: no peso, na altura de epitélio, na porcentagem dos componentes glamdulares (lúmen, epitélio e estroma), na quantidade de células receptor de andrógeno positiva e células em processo de proliferação e morte, bem como variações hormonais. Indicando assim que o nível de testosterona influencia nessas variações. A castração (supressão de testosterona) e a subsequente suplementação deste hormônio podem elucidar a relação das GRAs com a testosterona. Assim, o objetivo deste estudo foi avaliar o efeito da castração e suplementação de testosterona nas GRAs de A. planirostris. Os animais foram coletados na cidade de São José do Rio Preto, no noroeste do Estado de São Paulo, Brasil. As capturas foram realizadas no verão (21 de dezembro - 21 de março), a fim de minimizar as variações decorrentes da sazonalidade. Foram utilizados apenas machos adultos, com a determinação da idade dos animais baseada no peso corporal, ossificação completa das epífises metacarpo-falange, desgaste dos dentes, o posicionamento dos testículos e na presença de espermatozoides no testículo, cauda do epidídimo e/ou na uretra. Neste trabalho foram analisados quarenta e seis espécimes machos sexualmente maduros, os quais foram divididos em oito grupos: I) 3 dias castrado (CA3d, n = 7); II) controle três dias (CO3d, n = 4); III) 15 dias castrado (CA15d, n = 7); IV) 15 dias controle (CO15d, n = 5)...
Keywords: Biologia; Morcego - São José do Rio Preto; Castração; Testosterona; Próstata